A rapid expansion of hospitals: the adaptation of multi-campus hospitals under the Chinese healthcare system - Zhu, Xingchen; Yan, Xianliang (Frontiers in Health Services, 2023)
In recent years, China's healthcare system has undergone significant changes to meet the increasing demands of its growing population. One notable development is the rapid expansion of hospitals, particularly the adaptation of multi-campus hospitals. These multi-campus hospitals have become increasingly popular due to the many advantages that single-campus hospitals lack, including the ability to; improve medical service quality, reduce operating costs, and facilitate the development of healthcare services in rural areas. In this study, we discuss the advantages that this type of medical facility offers and identify existing and potential problems that could hinder the development of multi-campus hospitals. Additionally, we propose appropriate solutions to mitigate these problems. Overall, we propose that there should be more communication between multi-campus hospitals and other healthcare providers.